Replanteando la acción social por la música la búsqueda de la convivencia y la ciudadanía en la Red de Escuelas de Música de Medellín - Baker, Geoffrey (Open Book Publishers, 2022)
How can we better understand the past, present and future of Social Action for Music (ASPM)? This groundbreaking book examines the development of La Red de Escuelas de Música de Medellín, a network of 27 schools founded in 1996 in Colombia's second largest city in response to its reputation as the most dangerous city on Earth. Inspired by El Sistema, the founding Venezuelan music education program, La Red is, however, remarkably different: its history is one of multiple reinventions and a continuous search to improve its educational offer and better achieve its social objectives. His insights and attempts at transformation shed valuable light on ASPM's past, present, and future. Based on a year of intensive fieldwork in Colombia and written by Geoffrey Baker, author of El Sistema: Orchestrating Venezuela's Youth (2014), this important volume offers new perspectives on ASPM and its evolution both in academia and in practice. It will be of interest to a wide variety of audiences: employees and leaders of ASPM programs; music educators; sponsors and political leaders; and students and scholars from fields such as ASPM, music education, ethnomusicology, and other related fields.